Investigation of the hyperfine structure of weak atomic Vanadium lines by means of Fourier transform spectroscopy. (28th April 2015) - Güzelçimen, F; Er, A; Öztürk, I K; Başar, Gö; Kröger, S; Tamanis, M; Ferber, R
Abstract: In continuation of our work on the investigation of the hyperfine structure (HFS) of atomic vanadium, we analyzed weak spectral lines in a Fourier transform spectrum that have not been investigated up to now. The main objective of this work was the determination of the magnetic dipole HFS constant A of the energy level at 15 103.784 cm −1, which was the only energy level with unknown A value up to the energy of 28 000 cm −1 . Additionally, other gaps in the data of magnetic dipole HFS could be filled in. The spectrum of vanadium–argon plasma in a hollow cathode lamp is recorded in the spectral range from 12 500 to 26 000 cm −1 or 800 to 380 nm, respectively. The HFS of 42 weak atomic vanadium lines has been analyzed. All these lines show only partially resolved or even completely unresolved HFS. Therefore for each line the HFS constant A of one level involved in the transition was fixed during the fit to a value known from literature. As a result, we have determined the magnetic dipole HFS constant A for 12 energy levels of even parity as well as for 17 energy levels of odd parity for the first time.